A Gender-Based Comparative Evaluation of O2O Food Delivery Characteristics : A Requirements Prioritization Approach - Agarwal, Vaibhav; Sahu, Rajendra; Pandey, Ashutosh (Indian Journal of Marketing, 2023)
This article intended to assess enablers and deterrents to online-to-offline (O2O) food delivery (OFD) use from users’ and non-users’ perspectives at the sub-dimension level. The study aimed to parallelly evaluate these sub-dimensions for both genders and provide a self-comparison of preferences. An online survey was conducted to obtain users’ preferences. Two hundred valid responses were analyzed using the simple ranking method of the requirements prioritization approach for ordinal data analysis. The findings revealed that females required comprehensive product details, ease of interface use, convenience in transactions, and overall hygiene at all stages. Privacy violation was reported as the most significant risk perceived by females. Male OFD users asked for safe food packaging and a good delivery experience but perceived the product performance failure as a severe risk. The inability to access food quality online was the top reason to avoid OFD use. The findings will help OFD operators and food-tech start-ups improve their operations by addressing specific issues. The article is unique as it followed an approach different from just establishing linear relations by analyzing ordinal data using the requirements prioritization technique.